Sustainable Energy Finance Market Study for Financial Sector in Nepal - International Finance Corporation (International Finance Corporation, Kathmandu, 2017)
The industrial sector in Nepal is one of the major sources of pollution and inefficient energy use. Nepal also suffers from inadequate investment in energy efficiency and renewable energy in the industrial sector. Therefore, the South Asia Enterprise Development Facility took the initiative to conduct a market study to understand the current energy efficiency and renewable energy potential of Nepal, and identify areas where financial institutions can invest for maximum impact. The following report is structured into nine sections. The first is the introductory section which provides an overall synopsis of the report. The second section provides an overview of the industrial policy and policies related to energy efficiency/renewable energy technology. Section three of the report begins with a brief overview of industrial development in Nepal, including classification of industries (as per Industrial Enterprises Act 1992) based on fixed assets, energy demand, energy consumption by fuel type, and historical trend of energy consumption in the industrial sector of Nepal. Section four of the report provides information on the types of energy used in each of the ten industrial sectors along with their energy consumption patterns, local and regional norms of selected sectors, and the international best practices. Section five presents a mapping of the financial industry, giving an overview of the financial sector in Nepal along with brief financial status of the sampled banks and financial institutions. Section six calculates the investment potential and financing needs and lists the key barriers to sustainable energy finance based on the options identified and the cost estimation made in section four. Section seven proposes various types of financing mechanisms on the basis of industry-specific situation present in the country. Section eight presents the recommendations and conclusions of the study and section nine covers the limitations of the study. The details of the approach and methodology adopted for this study are presented in Annex 1; and the structured questionnaires designed for stakeholder interviews are presented in Annex 2.